Hormonal replacement therapy in posmenopausal women and neutrophils selected functions - TNF-α preactivation - Stachowiak, Grzegorz; Surkont, Grzegorz; Romanowicz-Makowska, Hanna; Połać, Ireneusz; Jędrzejczyk, Sławomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Objective: To evaluate effects of selected HRT in postmenopausal women on priming of neutrophils by TNF-α, measured in peripheral blood using the method of chemiluminescency. Material and methods: Study group consists of 46 postmenopausal women diagnosed and treated in Outpatient Clinic and Clinical Department of Gynaecology and Menopausal Diseases in our Institute. Oxydative burst of neutrophils was evaluated in 20 ml peripheral blood sample before, after 3 and 6 months of this therapy. Oxydative burst was observed after neutrophils acivation with stimulators: fMLP, PMA and zymosan with or without previous preactivation with 10 ng TNF-α. Chemiluminescency associated with oxydation burst was measured with Luminometr 1251, BioOrbit, Turku, Finland in stable temperature during 30 minutes (15 readings). Results: After 3 months of HRT treatment priming with TNF-a decrecreased by 13, 30.4, 30.9 i 27.9%, and after 6 months by 16, 28.9, 29.9 i 27.4% (p<0.0005). Conclusions: Hormonal replacement therapy has influence on neutrophils priming by TNF-α. After therapy priming is decreased.